2019
DOI: 10.1158/1538-7445.sabcs18-p6-18-20
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-18-20: Targeting mitochondrial function for the treatment of triple negative breast cancer: Development of a small molecule inhibitor against mitochondrial STAT3

Abstract: Background: Patients with Triple Negative Breast Cancer (TNBC) can benefit significantly from earlier diagnosis/prognosis, targeted therapy, and predictive biomarker panels for optimal therapy. However, currently there are no clinically accepted markers for the prognosis of TNBC and to predict its potential to metastasize. It is well documented that numerous cancer subtypes with increased mitochondrial oxidative phosphorylation in which enhanced mitochondrial activity is linked to aggressiveness. Also, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Basal subtype also enriches oxidative phosphorylation pathway. Clinical studies have shown that targeting oxidative phosphorylation provides an effective way to treat basal subtype ( 31 , 32 ). Glyoxylic acid and dicarboxylic acid pathways are highly expressed in basal breast cancer ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…Basal subtype also enriches oxidative phosphorylation pathway. Clinical studies have shown that targeting oxidative phosphorylation provides an effective way to treat basal subtype ( 31 , 32 ). Glyoxylic acid and dicarboxylic acid pathways are highly expressed in basal breast cancer ( 33 ).…”
Section: Resultsmentioning
confidence: 99%
“…MDC-1112 reduces the accumulation of mitochondrial STAT3 and induces apoptosis in pancreatic cancer cells [64]. In-house mitochondriatargeted tamoxifen (MitoTam) could suppress the phosphorylation of nuclear and mitochondrial STAT3, leading to proliferation inhibition and apoptosis in triple-negative breast cancer (TNBC) in vitro and in vivo [65]. Additionally, OPB-51602 results in mitochondrial dysfunction and cell death in human prostate cancer cells by interference with mitochondrial STAT3 [66].…”
Section: Discussionmentioning
confidence: 99%